2019
DOI: 10.1002/etc.4551
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem Controls on Methylmercury Production by Periphyton Biofilms in a Contaminated Stream: Implications for Predictive Modeling

Abstract: Periphyton biofilms produce a substantial fraction of the overall monomethylmercury (MMHg) flux in East Fork Poplar Creek, an industrially contaminated, freshwater creek in Oak Ridge, Tennessee. We examined periphyton MMHg production across seasons, locations, and light conditions using mercury stable isotopes. Methylation and demethylation rate potentials (km, trans av and kd, trans av, respectively) were calculated using a transient availability kinetic model. Light exposure and season were significant predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Recent studies suggested a transient availability rate potentials calculation, a modification of the original Hg methylation kinetic model from H. Hintelmann et al ( 43 ) through the determination and addition of sorption reaction kinetics, leading to k m 15 times higher than the full availability rate potentials ( 29 , 44 ). However, the remoteness of our sites and field laboratory has prevented the determination of such additional sorption constants to fit the equations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggested a transient availability rate potentials calculation, a modification of the original Hg methylation kinetic model from H. Hintelmann et al ( 43 ) through the determination and addition of sorption reaction kinetics, leading to k m 15 times higher than the full availability rate potentials ( 29 , 44 ). However, the remoteness of our sites and field laboratory has prevented the determination of such additional sorption constants to fit the equations.…”
Section: Resultsmentioning
confidence: 99%
“…The hgcAB genes were detected in periphyton from a high-altitude tropical lake ( 5 ) and subtropical wetlands of the Florida Everglades ( 26 ) with a predominance of sulfate reducers, methanogens, and syntrophs as putative Hg methylators. In addition to the genetic evidence of diverse methylator communities in periphyton, studies using isotopic approaches to estimate Hg transformation kinetics have shown that temperature, depth, light exposure, extracellular ligand concentrations, and biofilm structure are all factors influencing Hg methylation rates in periphyton ( 5 , 6 , 27 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…To further explore the role of periphyton biofilms in Hg cycling, biofilms were grown in the creek, returned to the lab, and amended with enriched stable isotopes of inorganic 201 Hg and Me 202 Hg (Olsen et al 2016, Schwartz et al 2019. The production of isotopically labeled Me 201 Hg and loss of Me 202 Hg was monitored over time as measures of Hg methylation and MeHg demethylation, respectively (figure 11).…”
Section: Field-informed Laboratory Experiments Identify a Dominant So...mentioning
confidence: 99%
“…WEOC was measured on a total organic carbon analyzer (TOC, Shimadzu) after the samples were acidified in 0.1% HCl and purged to remove inorganic carbonates (Philben et al, 2019;Yang et al, 2016b), and the detection limit was ~0.31 µmol C g -1 dw. For statistical analyses, all data were validated for normality using Shapiro-Wilk test (Schwartz et al, 2019). Differences in Hg species distributions between the two soils were tested by the two-sample t-test.…”
Section: Chemicals and Chemical Analysesmentioning
confidence: 99%